Recurrent Low-Grade Gliomas: Does Reoperation Affect Neurocognitive Functioning?. Issue 2 (16th February 2022) - Ng, Sam; Lemaitre, Anne-Laure; Moritz-Gasser, Sylvie; Herbet, Guillaume; Duffau, Hugues
Abstract : BACKGROUND: Reoperations in patients with recurrent low-grade gliomas (RLGG) were proposed to control tumor residual and delay the risk of malignant transformation over time. OBJECTIVE: To investigate neurocognitive outcomes in patients with RLGG who underwent a second surgery with awake monitoring. METHODS: In this retrospective study, patients who underwent a second awake surgery for RLGG were included. Patients had presurgical and 3-mo postsurgical neuropsychological assessments. Data were converted into Z -scores and combined by the cognitive domain. Number of patients with cognitive deficits ( Z -score <−1.65), variations of Z -scores, and extent of resection (EOR) were analyzed. RESULTS: Sixty-two patients were included (mean age: 41.2 ± 10.0 yr). None had permanent neurological deficits postoperatively. Eight patients (12.9%) had a cognitive deficit preoperatively. Four additional patients (6.5%) had a cognitive deficit 3 mo after reoperation. Among other patients, 13 (21.0%) had a mild decline without cognitive deficits while 29 (46.8%) had no change of their performances and 8 (12.9%) improved. Overall, 94.2% of the patients returned to work. There were no correlations between EOR and Z -scores. Total/subtotal resections were achieved in 91.9% of the patients (mean residual: 3.1 cm 3 ). Fifty-eight patients (93.5%) were still alive after an overall follow-up of 8.3 yr. CONCLUSION: Reoperation with awake monitoring in patients with RLGG was compatible with an early recovery of neuropsychological abilities. Four patients (6.5%) presented a new cognitive deficit at 3 mo postoperatively. Total/subtotal resections were achieved in most patients. Based on these favorable outcomes, reoperation should be considered in a more systematic way.